ChemInform Abstract: Reversible Topochemical Exsolution of Iron in BaFe2+2(PO4)2. Issue 11 (March 2015) - David, Renald; Kabbour, Houria; Filimonov, Dmitry; Huve, Marielle; Pautrat, Alain; Mentre, Olivier
Abstract Both long‐term air exposure of BaFe2(PO4)2 and moderate temperature of <375 °C leads to topochemical oxidation yielding iron‐depleted compounds BaFe2‐x(PO4)2 with mixed FeII/FeIII valence.